Bitcoin flash crash on May 19, 2021: What did really happen on Binance? - Tim Baumgartner; André Güttler (Halle Institute for Economic Research (IWH), 2022)
Bitcoin plunged by 30% on May 19, 2021. We examine the outage the largest crypto exchange Binance experienced during the crash, when it halted trading for retail clients and stopped providing transaction data. We find evidence that Binance back-filled these missing transactions with data that does not conform to Benford's Law. The Bitcoin futures price difference between Binance and other exchanges was seven times larger during the crash period compared to a prior reference period. Data manipulation is a plausible explanation for our findings. These actions are in line with Binance aiming to limit losses for its futures-related insurance fund.
urn:nbn:de:gbv:3:2-922372
Keywords: G10; G12; G14; K22; 330; Benford's law; Binance; Bitcoin; cryptocurrency; crypto exchange; derivatives; extreme volatility; fraud; market crash; trading outage